Modulation of miR-429 during osmotic stress in the silverside Odontesthes humensis - Pagano, Antônio D.; Barreto, Bruna F.; Domingues, William B.; Silveira, Tony L. R.; Nunes, Leandro S.; Blodorn, Eduardo B.; Dellagostin, Eduardo N.; Remião, Mariana H.; Robaldo, Ricardo B.; Campos, Vinicius F. (Frontiers in Genetics, 2022)
Silverside fish inhabit marine coastal waters, coastal lagoons, and estuarine regions in southern South America. Although silversides are not fully adapted to freshwater, they can tolerate a wide range of salinity variations. MicroRNAs (miRNAs) are a class of ∼22 nucleotide noncoding RNAs, which are crucial regulators of gene expression at post-transcriptional level. Current data indicate that miRNAs biogenesis is altered by situations of environmental stress, thereby altering the expression of target mRNAs. Foremost, the silversides were acutely exposed to 30 g.L−1 of salt to reveal in which tissue miR-429 could be differentially expressed. Thus, fish were acclimated to freshwater (0 g.L−1) and to brackish water (10 g.L−1), and then exposed to opposite salinity treatment. Here, we reveal that miR-429, a gill-enriched miRNA, emerges as a prime osmoregulator in silversides. Taken together, our findings suggest that miR-429 is an endogenous regulator of osmotic stress, which may be developed as a biomarker to assist silverside aquaculture.